The Role of Educational Psychology for Teachers in Learning Effectiveness - Azura, Yuni; Tarsono, Tarsono; Hermawan, A. Heris; Ningsih, Arum (Islamic Religious Education Study Program Postgraduate Program UIN Sunan Gunung Djati Band, 2022)
This study is blackfaced with problems in learning processes, such as teachers do not understand the student's situation and condition, they apply incorrect methods, or the learning process tends boring. The important role of psychological education for teachers is to help them understand students' psychological aspects so that teachers have basic rules for applying effective learning techniques to particular student characteristics. This study aims to know the essential role of psychology for teachers in the learning process and the psychological scope for teachers in studying students. The study uses qualitative methods, which isa literature approach (library research). Researchers use documentaries to collect data. This study shows that teachers must study educational psychology. In educational psychology, there is much discussion of the problems associated with human development. So, as an educator, it is very important to understand educational psychology.Penelitian ini dilatar belakangi dengan adanya masalah dalam proses pembelajaran seperti guru tidak memahami situasi dan kondisi siswa, penerapan metode yang kurang tepat dan proses pembelajaran cenderung membosankan. Peran penting pembelajaran psikologi pendidikan bagi guru membantu dalam mempelajari aspek psikologis siswa agar guru memiliki aturan dasar untuk menerapkan teknik pembelajaran yang efektif yang diterapkan pada karakteristik siswa tertentu. Penelitian ini bertujuan untuk mengetahui peranan penting psikologi bagi guru dalam proses pembelajaran dan mengetahui ruang lingkup psikologi bagi guru dalam mempelajari siswa. Penelitian ini menggunakan metode kualitatif dengan jenis pendekatankepustakaan (Library Research). Peneliti menggunakan studi dokumenter untuk pengumpulan data dalam penelitian. Hasil penelitian ini menunjukan bahwa sangat penting bagi guru dalam mempelajari psikologi pendidikan. Dalam psikologi pendidikan, banyak sekali pembahasan tentang masalah-masalah yang berkaitan dengan perkembangan manusia. Sehingga, sebagai pendidik sangat penting memahami psikologi pendidikan.